Using 3D Printing Technology to Teach Cartilage Framework Carving for Ear Reconstruction - Jovic, Thomas H.; Combellack, Emman J.; Jessop, Zita M.; Whitaker, Iain S. (Frontiers in Surgery, 2020)
Objective: The aim of this study was to determine the validity of using a carvable 3D printed rib model in combination with a 3D printed auricular framework to facilitate the teaching, training and planning of auricular reconstruction. Design: 3D printed costal cartilages from ribs 6 to 9 were produced using a FormLabs Form3 Printer and used to make negative moulds. 2:1 silicone-cornstarch mixture was added to each mould to make 12 simulated 6-9th costal cartilages suitable for carving. 3D printed auricular frameworks were produced in polylactic acid using an Ultimaker 3 3D printer to demonstrate the component parts and constructed framework of an auricular reconstruction. Participants: 12 plastic surgery trainees attended a workshop in which they each attempted auricular reconstruction using the carvable models and 3D printed plastic models as a guide. All candidates completed a pre- and post-training questionnaire to assess confidence and comprehension of auricular reconstruction, and the suitability of the models for facilitating this teaching. Results: Only 42% of trainees (n=5) had observed an ear reconstruction in theatre prior to the training course. Statistically significant improvements in the appreciation of the different components that make an auricular framework (p<0.0001) and confidence in carving and handling costal cartilage (p<0.0001) were noted following completion of the training. Highly significant improvements in comprehension of the approach to ear reconstruction (p=0.006) and locating the subunits of a reconstructed ear from costal cartilage (p=0.003) were also noted. 100% of participants felt the 3D printed teaching aids directly enhanced their learning. Conclusions: Ear reconstruction is a complex, time consuming multi-stage operation demanding significant amounts of experience, planning and an appreciation of the 3D chondrocutaneous structure. In this study we have demonstrated the value of 3D printing in producing a suitable simulated costal cartilage model and as an adjunct to comprehending and planning a framework for auricular reconstruction.